(untitled) (SAARC Journal of Agriculture, 2021)
The molecular characterization of chilli germplasm was done based on estimation of genetic diversity among the germplasm by using SSR markers. Forty chilli germplasms were analyzed using eight SSR primers. The SSR primers produced 30 SSR loci with an average value of 3.75 alleles per SSR locus. The similarity index matrix ranged from zero to 2.74. Polymorphic information content (PIC) of the SSR primers ranged from 0.543 to 0.735 with an average value of 0.658. The highest number (five) of allele was observed in primer CAMS-647, whereas the primers CAMS-864, CAMS-880 and CAMS-885 showed lowest number (three) of allele. The smallest allele was found in case of primer CAMS- 236 (176 bp), while the longest allele was detected for the primer CAMS- 864 (288 bp). Based on similarity matrix using the un-weighed Pair Group Method of Arithmetic Means (UPGMA) dendrogram, chilli germplasms were grouped into four main clusters. SSR markers showed genetic variability in the studied chilli germplasm. SAARC J. Agric., 19(1): 1-13 (2021)